2013
DOI: 10.1177/1534735413510559
|View full text |Cite
|
Sign up to set email alerts
|

Rubus idaeus L Inhibits Invasion Potential of Human A549 Lung Cancer Cells by Suppression Epithelial-to-Mesenchymal Transition and Akt Pathway In Vitro and Reduces Tumor Growth In Vivo

Abstract: The metastasis of lung cancer is the most prevalent cause of patient death. Various treatment strategies have targeted the prevention of the occurrence of metastasis. The epithelial-mesenchymal transition (EMT) in lung cancer cells is considered a prerequisite to acquire the invasive/migratory phenotype and to subsequently achieve metastasis. However, the effects of Rubus idaeus on cancer invasion and the EMT of the human lung carcinoma remain unclear. In this article, we test the hypothesis that R idaeus ethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…It is well known that berries contain phytochemicals with various biological properties such as anti-oxidant, anti-inflammatory and anticancer activities. Prior studies have demonstrated that extracts from berries can inhibit the growth of many human tumor cell lines, including those of lung, breast, colon, and prostate cancers (Seeram et al, 2006;Chu et al, 2014). In addition, berry extracts have been shown to stimulate apoptosis of a colon cancer cell line (Seeram et al, 2006), suggesting that these natural products can suppress the process of tumorigenesis via multiple pathways.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well known that berries contain phytochemicals with various biological properties such as anti-oxidant, anti-inflammatory and anticancer activities. Prior studies have demonstrated that extracts from berries can inhibit the growth of many human tumor cell lines, including those of lung, breast, colon, and prostate cancers (Seeram et al, 2006;Chu et al, 2014). In addition, berry extracts have been shown to stimulate apoptosis of a colon cancer cell line (Seeram et al, 2006), suggesting that these natural products can suppress the process of tumorigenesis via multiple pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we found that a higher concentration of RIE was more effective in suppressing NPC cell migration and invasion, suggesting that consumption of more Rubus idaeus as an adjuvant therapy may offer better efficacy in inhibiting metastasis. RIE has been shown to exhibit weak cytostatic effects on human cells at a concentration below 100 μg/mL (Hsieh et al, 2013;Chu et al, 2014), and thus the experimental concentrations of the extract used in the present study should be feasible in a clinical setting. Moreover, previous studied have shown that gallic acid, epigallocatechin (EGC), and catechin are the active substances in RIE (Hsieh et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Zhang et al, indicated that black raspberry can inhibit the growth of cervical cancer cells and induce cancer cell apoptosis (Zhang et al, ). Lung cancer‐related studies have shown that raspberry can effectively prevent cancer invasion and reduce the rate of lung‐cancer growth in mice by inhibiting epithelial‐to‐mesenchymal transition (EMT), achieving positive treatment outcomes (Chu et al, ; Hsieh et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The blot was subsequently operated with standard procedures and probed with primary and secondary antibodies. Protein expression was detected by chemiluminescence using an Immobilon Western Chemiluminescent HRP Substrate kit [23].…”
Section: Western Blot Analysismentioning
confidence: 99%